Truth telling for patients with esophageal squamous cell carcinoma in Henan, China - Lian-Qun Zhang; Pei-Nan Chen; Hai-Ling Wang; Li Sun; Xue-Ke Zhao; Xin Song; Min-Jie Wu; Tang-Juan Zhang; Ling-Fen Ji; Wei-Li Han; Zong-Min Fan; Yuan Yuan; et al. (Cancer Biology & Medicine, 2017)
Objective : This study aims to investigate the truth-telling status and the relevant factors of esophageal squamous cell carcinoma (ESCC) patients in Henan, China.Methods : A cross-sectional study from April to June 2015 using questionnaires was given to 301 family members of hospitalized ESCC patients based in three affiliated hospitals of Zhengzhou University (i.e., The First Hospital, The Second Hospital, and Tumor Hospital) and Anyang Tumor Hospital.Results : Among the 41.9% (126/301) hospitalized ESCC patients who knew of their true diagnoses, only 4.0% patients were informed by their corresponding responsible doctors, 39.7% by their family members, and 56.3% by themselves. Univariate analyses showed that disclosure of confirmed ESCC diagnosis to patients was correlated with gender, family history of cancer (FHC), education level, vocation, hospital administrative level, and attitudes of family members (P < 0.05). Furthermore, multivariate analysis indicated that attitude of family members was the most important and an independent factor for diagnosis disclosure. Those patients with a negative FHC, under-education, manual occupation, advanced stages, and hospitalized in municipal hospitals exhibited a low rate of truth telling.Conclusions : Truth telling for ESCC patients in Henan is not prevalent and may be improved through consultation with family members, particularly for patients with a negative FHC, poor education, manual occupation, and advanced stages.